Molecular dynamics analysis of a flavoring drum combining numerical simulation and experimental evaluation. (January 2023) - Liao, Hebin; Lin, Tianqin; Gardoni, Paolo; Zhang, Wei; Li, Xiaogang; Królczyk, Grzegorz; Deng, Lei; Li, Z.X.
Abstract: The tobacco flavoring process is an important procedure in production stage. During the flavoring process, the cut tobacco is endowed with a unique flavor to stabilize the production quality. Most of the flavoring process in tobacco enterprises is finished in the drum, and the internal structure of the drum (including the number, angle and installation position of the baffle plate) will affect the flavoring effect and efficiency. Therefore, this paper studied the particle behavior of the cut tobacco in the drum based on molecular dynamics analysis to explore the influence of the drum structure on the flavoring effect and to find the optimal structure parameters. Based on the discrete element simulation, an original rotary drum is structurally modified twice, and the corresponding field test is carried out to evaluate the performance of the modified drum. The results suggest that the flavoring effect is significantly improved through the structural modification, the content of menthol and citronellol are increased by 24.70% and 23.74% in the first test after modification, and reached 83.2% and 85.4% of the theoretical value respectively, and the error of the running time in the drum between the simulation and the test result is only 6.3%